Annual Flood Phenomenon and Fertility Status of Rice Soil in The Coastal Area of Bengkulu - Putra, Dio Rizki Ade; Sulistyo, Bambang; Barchia, Muhammad Faiz; Utami, Kartika; Rauf, Abdul (BPFP Universitas Bengkulu, 2024)
[ANNUAL FLOOD PHENOMENON AND FERTILITY STATUS OF RICE SOIL IN THE COASTAL AREA OF BENGKULU]. The rice fields in Rawa Makmur Village were agricultural land that was affected by annual floods. Soil fertility status is important for increasing the productivity of paddy. The research aimed to get the fertility status of soil affected by annual flood disasters, evaluating and mapping the distribution of soil fertility status at the research location. The methods used in this research include survey and soil testing methods at the Soil Science Laboratory, Faculty of Agriculture, Bengkulu University. Further evaluation of soil fertility status is in accordance with technical instructions from the Soil Research Center, Bogor (1995). This research was conducted in June – August 2023. The soil CEC value from each sampling point was classified as high with values ranging from 28.15 me/100 g - 39.83 me/100 g. The base saturation value in the study was classified as very low to moderate with values ranging from 11.49% - 40.08%. Soil organic C at the research location from each sampling point was classified as moderate to very high with values ranging from 2.42% - 5.97%. The soil phosphorus content at the research locations observed was classified as very low to low with values ranging from 2.69 mg/100 g – 12.11 mg/100 g. The soil potassium content at each sample point at the research location observed was classified as very low with values ranging from 0.14 mg/100 g – 1.43 mg/100 g. The research results show that the flood phenomenon has a significant impact on soil fertility. The soil fertility status at the research location is classified as low. Soil fertility parameters which are limiting factors in the status of soil fertility in Rawa Makmur Village are phosphorus, potassium and pH. So it is necessary to add P and K fertilizer to improve the soil fertility status.